Low-frequency generation by ionizing femtosecond laser pulse supplied by its second or half-harmonic - Laryushin, I.D.; Kuznetsov, L.S.; Kostin, V.A.; Silaev, A.A.; Vvedenskii, N.V. (Вопросы атомной науки и техники, 2015)
We calculate the free-electron residual current density excited in a gas by ionizing two-color femtosecond laser pulses containing an intense component centered at 800-nm and a weaker 400-nm (second-harmonic) or 1600-nm (half-harmonic) component with the use of quantum-mechanical (with the three-dimensional time-dependent Schrödinger equation solved numerically) and semiclassical approaches. The efficiency of residual current excitation by two-color pulses with additional second- and half-harmonic components is compared. З застосуванням квантово-механічного (заснованого на числовому розв’язанні тривимірного нестаціонарного рівняння Шрьодингера) та полукласичного підходів розрахована залишкова густина струму вільних електронів, що збуджена в газі двокольоровими лазерними імпульсами, які складаються з сильного основного поля з довжиною хвилі 800 нм та більш слабкого додатку другої (400 нм) або половинної (1600 нм) гармонік. Проведено порівняння ефективності збудження залишкового струму двокольоровими імпульсами з додатком другої та половинної гармонік. С использованием квантово-механического (основанного на численном решении трёхмерного нестационарного уравнения Шрёдингера) и полуклассического подходов рассчитана остаточная плотность тока свободных электронов, возбуждаемая в газе двухцветными лазерными импульсами, содержащими сильное основное поле с длиной волны 800 нм и более слабую добавку второй (400 нм) либо половинной (1600 нм) гармоник. Проведено сравнение эффективности возбуждения остаточного тока двухцветными импульсами с добавкой второй и половинной гармоник.